2015
DOI: 10.1007/s10646-015-1492-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations of bacterial community and its relationship with water chemistry in Sanya Bay, South China Sea as determined by DGGE fingerprinting and multivariate analysis

Abstract: Bacteria play important roles in the structure and function of marine food webs by utilizing nutrients and degrading the pollutants, and their distribution are determined by surrounding water chemistry to a certain extent. It is vital to investigate the bacterial community's structure and identifying the significant factors by controlling the bacterial distribution in the paper. Flow cytometry showed that the total bacterial abundance ranged from 5.27 × 10(5) to 3.77 × 10(6) cells/mL. Molecular fingerprinting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our research in Jinan also shows that NH 3 ‐N is an important factor affecting the structure index of food web. In the study of the impact of COD on aquatic ecosystems, Ling et al's (2015) research in Sanya Bay, China, obtained a significant correlation between COD and the spatial variability of bacterial communities through a large amount of data analysis. Yang et al (2012) collected a large number of data of aquatic organisms in the Taihu Lake Basin of China and found that COD affected the structure and community of Microcystis in Taihu Lake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research in Jinan also shows that NH 3 ‐N is an important factor affecting the structure index of food web. In the study of the impact of COD on aquatic ecosystems, Ling et al's (2015) research in Sanya Bay, China, obtained a significant correlation between COD and the spatial variability of bacterial communities through a large amount of data analysis. Yang et al (2012) collected a large number of data of aquatic organisms in the Taihu Lake Basin of China and found that COD affected the structure and community of Microcystis in Taihu Lake.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the conclusion that the NH 3 -N can promote the maturity of the food web structure in our study. In the study of the impact of COD on the ecosystem, Ling et al (2015) found that COD promotes bacterial abundance in the study of the spatial variability of bacterial communities and their relationship with water chemistry in South China Sea Sanya Bay. The result is different from the conclusion that in our study, mainly because COD has a positive effect on the abundance of the bacterial community, but our study focuses on the entire food web organization.…”
Section: Analysis Of Nonpoint Source Pollution On Food Web Structurementioning
confidence: 99%
“…Water that was filtered through 0.45 lm pore size cellulose acetate filters (GE Whatman, Sigma-Aldrich Inc., MO, USA) was used to analyze the concentrations of total nitrogen (TN), total phosphorus (TP) ammonium (NH 4 þ ), nitrate (NO 3 À ) and phosphate (PO 4 3À ) via continuous flow analysis on a San þþ automated wet chemistry analyzer (Skalar Analytical B.V., Breda, Dutch) at wavelengths of 540, 880, 660, 540 and 880 nm, respectively, based on protocols provided by the manufacturer. All other physiochemical parameters, including chlorophyll a (Chl-a), chemical oxygen demand (COD), turbidity (Turb), alkalinity (ALK) and water transparency (SD), were determined by the methods as described previously (Ling et al 2015).…”
Section: Analysis Of Environmental Characteristicsmentioning
confidence: 99%